The influence of transformational leadership dimensions toward employee performance through the mediating variables job satisfaction and employee engagement - Ambarwati, Agustin; Wahyudi, Triyono Arief (Jurnal STEI Ekonomi, 2024)
The aim of this research is to further analyze the effect of the Transformational Leadership dimension on Employee Performance through the variables of Job Satisfaction and Employee engagement in health insurance employees. Data collection was carried out by purposive sampling at BPJS Health with sample criteria, namely employees with staff positions who have worked for at least 2 years spread across branch offices in region IV. The research was conducted quantitatively using the Structural Equation Model (SEM) method in 2023 using 310 respondents. The results of this study prove the influence between all dimensions of Transformational Leadership on job satisfaction, as well as the influence of job satisfaction variables on employee performance and the influence of variables intellectual stimulation, Inspirational Motivation and Individual Consideration on work engagement. This study also proves the absence of idealized influence on work engagement and employee performance and the dimension of Transformational Leadership intellectual stimulation on employee performance and work engagement on employee performance.